Efektivitas Sistem Threshold dalam Presidential Threshold di Indonesia - Harlian Satria Wilwatikta; Falah Ramadhani; Malik Madya Jaya Pratama; Dzaqyar Rahmatul Iqbal; Fauzan Adhima; Hillan Rusydha Fazha (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The Presidential Threshold is a rule that sets the minimum threshold percentage of votes that a political party is required to achieve, in order to nominate or carry presidential and vice presidential candidates in the election contestation. This system is designed to filter out candidates who are considered qualified, the hope is that only candidates with high electability levels can run. However, its implementation is often a source of controversy because it is considered to hamper potential candidates from small parties or independents who may have quality, but are less known to the public. As a result, the dominance of major parties in the presidential candidacy limits people's choices and does not reflect the existing political diversity. In the Indonesian system of government, where the president and the DPR are independent institutions, the Presidential threshold system is considered incompatible with the principles of inclusive and representative democracy. This provision was first implemented through Article 5 paragraph (5) of Law Number 23 Year 2003 on the General Election of the President and Vice President, and has continued to be used in subsequent presidential elections. This article focuses on the effectiveness of the Presidential Threshold in the Indonesian political context and its impact on political participation, democratic representation, and constitutional law.